Variable loss of CD30 expression by immunohistochemistry in recurrent cutaneous CD30+ lymphoid neoplasms treated with brentuximab vedotin. (2nd August 2019) - Goyal, Amrita; Patel, Sanjay; Goyal, Kavita; Morgan, Elizabeth A.; Foreman, Ruth K.
Abstract: Aims: Brentuximab vedotin is a monoclonal anti‐CD30 antibody‐drug conjugate that has been used to treat a variety of CD30+ neoplasms. The phenomenon of antigen loss has been observed in patients treated with the anti‐CD20 antibody rituximab. This study seeks to assess for antigen loss in the setting of recurrent CD30+ neoplasms treated with brentuximab vedotin. Methods: We report nine cases of persistent/recurrent cutaneous CD30+ lymphoid neoplasms that demonstrated variable CD30 expression after treatment with brentuximab vedotin. Cases include MF (n = 6), cutaneous T‐cell lymphoma, not otherwise specified (n = 1), and anaplastic large cell lymphoma (ALCL), both primary (n = 1) and systemic (n = 1). Results: Immunohistochemical staining revealed decreased CD30 expression following brentuximab vedotin therapy in seven of nine cases. In these seven cases, the pre‐treatment percent of tumor cells staining for CD30 ranged from 10% to 100% (mean 50.0%, SD 27.8%), compared to 5% to 50% (mean 14.5%, SD 14.8%, P = 0.003) at recurrence. Conclusions: This case series highlights the finding that CD30 positivity can be variable in recurrences after treatment with anti‐CD30 antibodies. This serves to raise awareness of the phenomenon of antigen loss after treatment with brentuximab vedotin and underscores the utility of performing multiple biopsies and/or employing molecular diagnostic techniques in patients with recurrent/persistent disease.